Pengaruh Relaksasi Pernapasan Terhadap Intensitas Nyeri pada Persalinan Kala I di Puskesmas Pagar Merbau Kec. Pagar Merbau Kab. Deli Serdang Tahun 2023 - Siti Hapsah; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Mothers who have difficulty adapting to labor pain can cause uterine contractions to become uncoordinated, which risks prolonging the first phase of labor and disrupting fetal well-being. This study aims to analyze the effect of breathing relaxation techniques on the intensity of labor pain in the first stage at the Pagar Merbau Health Center, Pagar Merbau District, Deli Serdang Regency in 2023. This study used a quantitative method with a One Group Pre-Test Post-Test design. The study population included all mothers giving birth in the period from April to June 2023, with a sample size of 15 respondents. The results showed that before the intervention, there were 2 respondents (13.3%) who experienced mild pain, 6 respondents (40.0%) with moderate pain, and 7 respondents (46.7%) experienced severe pain. After the intervention, the number of respondents with mild pain increased to 8 people (53.3%), moderate pain decreased to 4 people (26.7%), and severe pain decreased to 3 people (20.0%). The results of this study indicate a significant change in the level of pain in mothers giving birth before and after treatment. Therefore, it is expected that midwives at the Pagar Merbau Health Center can optimize the application of breathing relaxation techniques as a method to reduce labor pain, especially in the first phase of labor.